Representaciones sociales en el cantón Saquisilí sobre las personas privadas de libertad a partir de la implementación del centro de rehabilitación social de Cotopaxi. - Cajamarca Pila, Katherine Lizeth (2018)
The problem related to convicts requires an urgent analysis. In addition, it is a thematic that has been insufficiently studied from the field of communication. In this sense, the objective of this project is to identify the social representations that are generated about Personas Privadas de la Libertad (ppl) in the population of Saquisili, taking as a reference the construction and inauguration of Cotopaxi Social Rehabilitation Center in february, 2014. The methodological strategy that was implemented had a qualitative approach through the technique of discussion groups: in the first group, social actors participated who gave us their perspective from the institutional field, while in second group, neighbors who live near the Center of Social Rehabilitation participated. The main results show that social representations of convicts are marked by the demand for greater state intervention through public policies that allow them to reinsert themselves effectively into their social environment. In addition, a recurrent idea is the stigmatization of (ppl) families because they are stigmatized as a risk group. One of the main conclusions note the importance of the role of the State in the generation of strategies that contribute to adequate processes of social rehabilitation, support actions for families, and mechanisms that allow facing the impact that the construction of a prison center generates for a specific population.